DA CONCILIAÇÃO TRABALHISTA À RESISTENCIA BRIZOLISTA: POLÍTICA, VIOLÊNCIA E O SURGIMENTO DA INFLUÊNCIA DE LEONEL DE MOURA BRIZOLA EM CHAPECÓ, SANTA CATARINA (1950-1965) - Rigo, Carla Aparecida (2017)
The present work aims to understand the influence of the politician Leonel de Moura Brizola in the politics of Chapecó-SC, having as main focus the period from 1961 to 1964 with the military coup. Still, trying to understand how the same stood out in the region among several Brazilian politicians of the time and remained for decades as an important political tradition, more known and influential than the own Getúlio or Jango tradition. This research, in this sense, intends to dialogue with works that approach the local politics and that deal with the formation politics. Recalling that violence has always been present in the western region of Santa Catarina and that it will be one of the elements used in research as a way of maintaining economic, political and social power. In addition, the documentation on political history present in the regional archives is small, mainly in relation to the theme brizolismo and the formation of the Group of the Eleven Companions under influence of Brizola. However, as the Group of Eleven existed in the region, or at least existed in the eyes of those who persecuted the petebistas, we considered this to be the high point of Leonel Brizola's influence in the region before his political exile in 1964, shortly after the military coup.